The Mediterranean fruit fly and its bacteria – potential for improving sterile insect technique operations. (24th June 2010) - Yuval, B.; Ben‐Ami, E.; Behar, A.; Ben‐Yosef, M.; Jurkevitch, E.
Abstract: Mediterranean fruit flies ( Ceratitis capitata Wiedemann, Diptera: Tephritidae), harbour a diverse community of bacteria in their digestive system. Molecular and culture‐based techniques show that members of the Enterobacteriaceae form the dominant populations in the gut of the Mediterranean fruit fly. Among them, many are diazotrophs and actively fix nitrogen in vivo . Most prominent are Klebsiella spp., Enterobacter spp., Pectobacterium spp. Citrobacter freundii and Providencia stuartii . A marked shift in community composition was observed between different developmental stages: in larvae, the pectinolytic Pectobacterium were most abundant, suggesting that pectinolysis plays a role early during the fly's life. Additionally, pseudomonads, some of which are known entomopathogens, constitute a minor, yet common and stable community in the C. capitata gut. Microbial communities in VIENNA 8 flies, a mass rearing genetic sexing strain, differ from wild flies, and irradiation further affects the microbial community. We found increased levels of the pathogenic species Pseudomonas in the industrially used strain. Furthermore, although members of the Enterobacteriaceae family remain the dominant bacteria group present in the fly's gut, the levels of Klebsiella species decrease significantly in the days after irradiation. Eliminating the bacterial population in normal flies by using antibiotics affects measurable physiological and behavioural parameters related to fitness. Finally, we tested the hypothesis that inoculation of sterile flies with members of the original bacterial community results in enhanced competitiveness. We found that addition of the bacteria Klebsiella oxytoca to the post‐irradiation diet significantly improves sterile male performance.